التعليم في عصر ملوك الطوائف قراءة في أماكن التدريس ومناهجه - بليل, الصالح (جامعة الوادي - University of Eloued, 2021)
يقوم هذا البحث بسبر أغوار المصادر والمؤلفات التي تحتفظ بنصوص تمكننا من رسم معالم العملية التعليمية بالأندلس في القرن الخامس الهجري مكانا ومنهجا وعلاقة ذلك بالنهضة العلمية التي طبعت هذا القرن، وقد اتضح لنا بأن المدرس في هذه الفترة قد تخلص من قيد المكان فلم يكن يقدم دروسه لطلابه في مكان لا يتجاوزه إلى غيره بل توسعت هذه العملية لتشمل أماكن مختلفة، وبذلك تعددت لدى الطالب فرص الحصول على المادة العلمية، أما بخصوص الطرق والمناهج التي كانت وسيلة الأستاذ لنقل العلوم والمعارف إلى الطالب فقد ظهرت إلى جانب المنهج القديم السائد أفكار تؤسس لمناهج وطرق يعتقد أصحابها أنها أكثر فعالية، حدث ذلك في قرن طغى عليه الانقسام السياسي والركود الاقتصادي والاقتتال بين أبناء الملة الواحدة. This research explores the depths of the sources and writings that retain texts that we were able to draw the milestones of the educational process in Andalusia in the fifth century AH, a place and a method, and its relationship to the scientific renaissance that marked this century, and it became clear to us that the teacher during this period had rid of the restriction of the place and was not providing his lessons to his students In a place that does not exceed it to others, but this process has expanded to include different places, and thus the student has multiple opportunities to obtain the scientific material, but regarding the methods and curricula that were the way of the teacher to transfer science and knowledge to the student has emerged alongside the prevailing old curriculum ideas that establish the curricula and methods believed by their owners It is more effective.
مقال
Keywords: التعليم؛ الأندلس؛ ملوك الطوائف؛ المدارس؛ المناهج; Education; Andalusia ; kings of Denominations ; Schools; Curricula